The Predictive Role of Perceived Autonomy Support in Elementary School Children Physical Activity - Mikel Vaquero-Solís; Miguel Ángel Tapia-Serrano; Pedro Antonio Sánchez-Miguel; Rubén Llanos-Muñoz; Miguel Angel López-Gajardo (MDPI AG, 2022)
The present article aimed to test a predictive model based on children's perception of autonomy support exercised by their physical education teachers in establishing a state of high motivational quality, which in turn leads to greater intention and physical activity. Participants were 502 elementary school students aged 9 to 11 years (52.59% males (9.47 ± 0.53 years old) and 47.41% females (9.54 ± 0.53 years old)), who completed a self-reported questionnaire of perceived autonomy support from physical education teachers, self-determination, intention to be physically active, and physical activity. Results showed that perceived autonomy support was positively related to autonomous motivation, which in turn was associated with intention and physical activity. In addition, the model did not present variations with respect to gender and confirmed the indirect effects of autonomous motivation on intention and practice of physical activity. Finally, we conclude on the importance of an adequate perception of autonomy support in students by their teachers for the establishment of an appropriate motivational state that could promote greater intention and physical activity. Thus, the motivational state acquired in physical education classes can be translated into intention and practice of physical activity in different contexts of students' daily lives.